Factors Related to the Risk of Occupational Stress among Nurses in the Emergency Room at Sosodoro Djatikoesoemo Bojonegoro Hospital - Rizqi Supramulyana Putra; Tya Nisvi Rahmadhani; Sho`im Hidayat (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: Occupational stress is a body response that is present in the form of physiological, psychological, and behavioral responses to stressors in the work environment. If this condition is not handled properly, it will have a negative impact on workers, and it can reduce the level of health and cause several diseases. The purpose of this research was to determine the risk of occupational stress among nurses in the Emergency Room at Sosodoro Djatikoesoemodan Hospital and what factors were related to the risk of occupational stress. Methods: This research is a descriptive observational study with respondents consisting of 26 nurses in the Emergency Room at Sosodoro Djatikoesoemo Hospital. Data collection was done using questionnaires to measure the level of occupational stress risk of nurses, which included variables of individual worker’s characteristics and job characteristics. The data analysis in this study used the Spearman correlation. Results: The results showed that 15.4% of nurses had a low level of occupational stress risk, 69.2% had a moderate level of occupational stress risk, and 15.4% had a high level of occupational stress risk. Moreover, there was a significant relationship between social support and workload factors on the risk of occupational stress. Conclusion: Most of the nurses experienced moderate occupational stress. Gender, personality type, workload and mental demands were factors that were related to the risk of occupational stress and could increase the risk of occupational stress. Meanwhile, interpersonal conflict and job control were elements that were not related to the risk of occupational stress.Keywords: emergency room Sododoro Djatikoesomo hospital, nurses, risk of occupational stress